Usefulness of adjunctive alpha1-adrenergic antagonists, after single extracorporeal shock wave lithotripsy session, in ureteral stone expulsion. - Janane, Abdellatif; Hamdoun, Abdelaziz; Hajji, Fouad; Dakkak, Youssef; Ghadouane, Mohamed; Ameur, Ahmed; Abbar, Mohamed (Canadian Urological Association Journal, 2014)
Introduction: We evaluate the efficiency of alpha-adrenergic antagonists on stone clearance after extracorporeal shock wave lithotripsy (ESWL) in patients with lower ureteral stones. Methods: A total of 356 patients with solitary lower ureteral stones who underwent single ESWL sessions were divided into 2 groups. Group 1 received our standard medical therapy, and Group 2 was treated with 0.4 mg/day tamsulosin for a maximum of 2 weeks. All patients were re-evaluated with plain film radiography and ultrasound each week during the treatment period. A computed tomography scan was systematically performed 3 months after ESWL. Results: In total, 82 of the 170 patients in Group 1 (48.2%) and 144 of the 186 patients in Group 2 (77.4%) (p = 0.002) were stone free. Among the patients with stones 10 to 15 mm in diameter, the stone-free rate was 38.4% in Group 1 and 77.1% in Group 2 (p = 0.003). Average stone expulsion time was 10.6 days and 8.4 days in Groups 1 and 2, respectively. Ureteral colic occurred in 40 patients (23.5%) in Group 1, but only in 10 patients (5.3%) in Group 2 (p = 0.043). The only side effect of tamsulosin was slight dizziness in 5 of the 186 patients in Group 2 (2.6%). Conclusion: Adjunctive therapy with alpha1-adrenergic antagonists after ESWL is more efficient than, and equally as safe as, lithotripsy alone to manage patients with lower ureteral stones. The adding of alpha-blockers is more reliable and helpful for stones with a large dimension, and can also decrease stone elimination time and episodes of ureteral colic.